Spiders on winter wheat and winter peas - Serhieiev, L.; Deli, O.; Uzhevska, S.; Burykina, S.; Rudenko, V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To determine the species composition of spiders of the cereal and legume agrocenosis of the Southern Steppe. Venue Experimental field of Odesa State Agricultural Experimental Station ICSA NAAS.Methods. Informational and analytical (collection of materials and analysis of literary sources), field research (collection and definition of material), mathematical and statistical (processing of research results). Research was conducted according to generally accepted methods in entomology and plant protection, starting from seedlings before the end of vegetation (end of November), beginning of vegetation (last days of February-beginning of March) until harvesting (end of June).Results. During the entire period of the study, 19 species of spiders belonging to 12 families were registered in the fields of the studied region, of which 2 species of spiders were noted for the first time for the Odesa region. The largest number of species of spiders was observed in control plots of winter wheat — 18 species from 12 families. After chemical treatment of wheat, the number of species of spiders was smaller — 9 species from 7 families. In the wheat fields that were treated with biological preparations, the number of spiders was lower than in the control, but higher than in the fields that were treated with chemical preparations. Of the 18 species of spiders that were noted in the control of the wheat fields, 9 species of spiders were not recorded in the collections after the fields were treated with chemical preparations. 11 species of spiders from 9 families were found on the control plots of winter-sowing peas, after chemical treatment of peas, the number of spider species was smaller — 9 species from 7 families. The spider Xysticus kochi dominated the pea plots that were treated with biological preparations, the number of specimens of this species was the highest.Conclusions. 19 species of spiders belonging to 12 families were registered in the cereal and leguminous agrocenosis of winter crops of the Southern Steppe during the entire period of the study. The spiders Aelurillus laniger Logunov & Marusik, 2000 (family Salticidae) and Ozyptila scabricula (Westring, 1951) (family Thomisidae) were discovered for the first time in Odesa region. In the control plots, where neither protective nor synthetic fertilizers were used, the number of species and the number of specimens of spiders was higher than in the fields treated with chemical and biological preparations.